Optimization Condition of Giant Magnetoresistance in Granular Thin Films for Application as Magnetic Sensors - Kabashi, Khatir Kabashi (2004)
The discovery of giant magnetoresistance (GMR) in multilayer systems and subsequently in granular films has stimulated worldwide research activities, due to both its fundamental significance and its potential application to magnetic sensors for fields ranging from 1 T up to 10 T. For granular films, however, there exists evidence that interface scattering plays a dominant role in magnetoresistance. The GMR is believed to be relating to the features of magnetic granules such as size, shape, and distribution. Concerning the effect of the feature of magnetic particle, most of the experimental work has focused on the post-deposition annealing, which is believed to promote grain growth or phase segregation. The need for new and improved optical and electronic devices has stimulated the study of CoNiAg, CoFeAg, and CoNiCu thin solid films with controlled composition and specific properties in this project. Therefore, a comprehensive investigations of the microstructure, structural, and magnetoresistance properties for the as deposited and annealed samples were performed via scanning electron microscopy (SEM), atomic force microscopy (AFM), energy disperssive spectroscopy (EDS), x-ray diffractometry (XRD), and four point probe techniques. The measurements were achieved at low and room temperatures in the presence of applied magnetic field of ~1.1 T. In response to these investigations, SEM micrographs have revealed that the surfaces of the films are smooth, uniform, and homogeneity with the presence of some impurities occurred after annealing, whereas AFM images showed that both the grain diameter and the RMS roughness were increased after annealing. EDS has determined the average chemical composition for each system, which shows fine dispersion of Co particles into Ag and Cu matrices in comparison with Fe and Ni particles. XRD spectrum has shown fcc structure for all as deposited and annealed samples with the respective peaks of (111), and (200) corresponding to the Ag plane in addition to the unknown peak related to the impurities appeared at 400°C and 500°C for CoNiAg system. For CoFeAg samples the broadened diffraction peaks roughly corresponded to the Ag (111), Ag (200), and Ag (220) reflections were detected due to the phase separation, whereas in the CoNiCu system two diffraction peaks corresponding to the (111), and (200) related to Cu plane in addition to the unknown peak at ~36°C have been observed in all series. The intensities and positions of these peaks for all series vary upon increasing the magnetic content and annealing temperature, indicating that the lattice parameter decreases with increasing magnetic content. For the best MR effect in these three systems, MR value at 100 K, increases from 0.75% in the as deposited samples to 1.45% in the annealed samples for CoNiAg system, for which the optimum annealing temperature, deposition time, and Co content were 400°C, 120 minutes and 16 at.% respectively. The MR ratios of 3.37% and 31.34% at 100 K, were obtained respectively in the as deposited and annealed samples of CoFeAg system for deposition time of 120 minutes, hence an optimum annealing temperature was located at 400 °C for optimum Co content of 12 at.%. While for CoNiCu system, the MR value increases from 0.41% for as deposited samples to 5.09% for annealed samples at 400°C. The optimum deposition time, annealing temperature, and Co content that provides the highest MR values are 120 minutes, 400°C, and 17 at.% respectively. Measurements at 300K also show MR values but lower than at 100K for all series. Among these systems, CoFeAg is the best, which shows the highest MR, while still under precise deposition conditions and proper thermal treatment, the other two systems may promise to show large MR effect.